ANALISIS PERANCANGAN TATA LETAK GUDANG BAHAN BAKU MENGGUNAKAN METODE SHARED STORAGE PADA PT. INDONESIA PLAFON SEMESTA - Farhan Kamil Mubarak; Suseno Suseno (JOURNAL SAINS STUDENT RESEARCH, 2024)
PT. Indonesia Plafon Semesta is a company engaged in the production and distribution of building materials in the form of ceilings made of Polyvinyl Clorida (PVC). At the beginning of April 2023, all activities in and out of goods that occur in the warehouse produce a total distance of 2659.5 m / day with a total Material handling Cost (OMH) of Rp. 6,871,200 / day, if this happens repeatedly within 1 month (26 working times) it will get a total distance of 69147 m with a total cost of Material handling (OMH) of Rp. 95,063,527. The layout of this warehouse also does not use an optimal layout, because it only places goods that come in empty space so that it hampers warehouse activities. The shared storage method is based on the condition of the warehouse floor area, then sorted the closest area to the area farthest from the I/O entrance so that the placement of goods that will be sent immediately is placed in the closest area and so on. The design of the right layout is by bringing the raw materials closer to the largest value based on the assignment value, using rectilinier calculations in the shared storage method obtaining a total distance of 2361.5 m / day, then for the resulting OMH which is Rp. 81,893,093 / month, thus the total distance from the warehouse area to the mixer area becomes 61.399 m / month